Implementasi Program Pencegahan Pemberantasan Penyalahgunaan Dan Peredaraan Gelap Narkoba (P4GN) Bidang Pemberdayaan Masyarakat BNNP Kalimantan Tengah: Implementation of drug eradication prevention and illegal Peredation Program (P4GN) of community Empowerment BNNP in central Kalimantan - Karyono, Kayono (Pencerah Publik, 2017)
The focus of this study is the implementation of P4GN program of Community Empowerment BNNP Central Kalimantan in SLTA Kota Palangkaraya. This is because the case of drugs involving the worship and students in 2015 amounted to 330 cases. The purpose of this research is to describe and analyze the implementation of P4GN program in the field of empowerment in the high school level top of Palangkaraya city and analyze the factors that are becoming an obstacle in implementing the program. This type of research is qualitative research. While the design of this research is case studies. The results showed that the implementation of P4GN program in the field of empowerment in Palangkaraya SLTA environment is already running well by the guidelines of implementation of P4GN program. The inhibitory factor of the implementation of the program is a matter of budget, human resources, the ability to understand the technical guidance of the implementation of p4GN programs in schools and the regulation related to the implementation of P4GN in the SLTA environment in the city Palangka Raya.